Anthelminthic Effect Of Date Palm Fruit: A Systematic Review - A. Rauf; F.H. Addnan; N.F.M. Manzor; W.O. Abdullah; M.A. Elkadi; F. Hamdan; K.N.N. Aripin; J.M. Behnke; Fadlul Azim Fauzi Mansur (New Century Health Publishers, LLC, 2024)
Indexed by Scopus